2022
DOI: 10.1021/acs.organomet.2c00333
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Effect in Binuclear Zinc Catalysts in the ROP of Lactide

Abstract: Me 3 and Et 4) and dimeric ketodiiminate zinc alkyl complexes [L 1 (H)ZnR] 2 (R = Me 5 and Et 6; L 1 = (Me 2 NC 2 H 4 NC (Me)CH) 2 CO, L 2 = (Me 2 NC 3 H 6 NC(Me)-CH) 2 CO) were synthesized and spectroscopically characterized ( 1 H and 13 C NMR and IR). Diffusion-ordered NMR spectroscopy and single-crystal X-ray diffraction analysis (1, 2, and 4−6) proved their monomeric (1−4) and dimeric (5 and 6) structures in solution and solid states. Their catalytic activity in the ring-opening polymerization of lactide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Recently, Schulz and co-workers reported the syntheses of ketodiiminate zinc-alkyl complexes (Figure 9) and studied their activity for the ROP of L-LA. 56 In general, bimetallic complexes 39−44 were highly active with the Zn-ethyl complexes giving enhanced TOF values compared to the Zn-methyl analogues, likely due to the higher nucleophilicity 9). These studies revealed that the transfer of the methoxy group to L-LA has a lower energy barrier for 50 compared to 49, as the second Zn center improves the activation of the carbonyl bond, resulting in faster polymerization.…”
Section: Multimetallic Catalysts For the Rop Of Cyclic Estersmentioning
confidence: 99%
“…Recently, Schulz and co-workers reported the syntheses of ketodiiminate zinc-alkyl complexes (Figure 9) and studied their activity for the ROP of L-LA. 56 In general, bimetallic complexes 39−44 were highly active with the Zn-ethyl complexes giving enhanced TOF values compared to the Zn-methyl analogues, likely due to the higher nucleophilicity 9). These studies revealed that the transfer of the methoxy group to L-LA has a lower energy barrier for 50 compared to 49, as the second Zn center improves the activation of the carbonyl bond, resulting in faster polymerization.…”
Section: Multimetallic Catalysts For the Rop Of Cyclic Estersmentioning
confidence: 99%
“…MALDI-ToF mass spectra were recorded with a Bruker UltraeXtreme MALDI-ToF Scheme 2 Catalytically active mono-and bimetalic catalysts I, II and III. 36,37,42 mass spectrometer (Bruker Daltonik). The polymers were dissolved in THF (10 mg mL −1 ) using dihydroxy benzoic acid as the matrix in THF (20 mg mL −1 ).…”
Section: General Experimental Detailsmentioning
confidence: 99%
“…26 In the last decades, main group metals such as alkaline or earth alkaline metals [27][28][29] as well as zinc have been intensively studied as catalysts for the ROP of lactides and lactones due to their high activity, low toxicity and biocompatibility. [30][31][32][33][34][35][36][37][38][39][40][41] In marked contrast, these type of metal complexes are rarely known for the preparation of cyclic polylactides. Recently, our group reported the synthesis of binuclear magnesium complexes and their capability for the synthesis of cPLA and cPCL with high TOF values up to 712 800 h −1 under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Metal alkoxides and derived phenolates, including those of Sn [7, 8], Al [9–11], Zn [12], Mg [13], Ti [14], and rare earth (Ln = Sc, Y, La‐Lu) compounds [15–17] have been reported as catalysts/initiators for the bulk ROP of different cyclic esters and lactides. In this work, we focus on the Ln complexes [18] which have been utilized to promote the ROP of cyclic esters with good catalytic performance [6, 19] for biomedical applications [20].…”
Section: Introductionmentioning
confidence: 99%